2021
DOI: 10.1016/j.jarmac.2021.07.002
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Face Masks on Forensic Face Matching: An Individual Differences Study

Abstract: In the forensic face matching task, observers are presented with two unfamiliar faces and must determine whether they depict the same identity. Due to the Covid-19 pandemic, some governmental authorities require the use of face masks in public spaces. However, face masks impair face identification by disrupting holistic processing of faces. The present study explores the effect of face masks on forensic face matching. Compared to a full-view condition, performance decreased when a face mask was superimposed on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 53 publications
1
14
0
Order By: Relevance
“…The use of intermixed method in presenting masked and unmasked faces may increase participants’ reliance on a pictorial matching strategy based on the top face half, mitigating the magnitude of face mask effects. This concern is supported by recent studies which demonstrated that most observers are capable of matching masked faces with remarkably high sensitivity (Estudillo et al, 2021 ) and developing strategies for coping with the unwarranted effects of face masks in blocked- than in mixed designs (Fitousi et al, 2021 ).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The use of intermixed method in presenting masked and unmasked faces may increase participants’ reliance on a pictorial matching strategy based on the top face half, mitigating the magnitude of face mask effects. This concern is supported by recent studies which demonstrated that most observers are capable of matching masked faces with remarkably high sensitivity (Estudillo et al, 2021 ) and developing strategies for coping with the unwarranted effects of face masks in blocked- than in mixed designs (Fitousi et al, 2021 ).…”
Section: Discussionmentioning
confidence: 92%
“…Some countries made it mandatory to wear masks when in public. While face masks are one of the best defences against the spread of respiratory virus, their growing adoption has posed a challenge not only to the way people interact with each other in social situations (Eikenberry et al, 2020 ), but also to human face recognition and perception (Carbon, 2020 ; Carragher & Hancock, 2020 ; Estudillo et al, 2021 ; Freud et al, 2020 ). Following the widespread use of face masks, the fundamental concerns pertain to difficulties in extracting facial identity and making social judgements on one’s characteristics (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Marini et al 4 demonstrated that unoccluded faces were reidentified more accurately when unoccluded faces, rather than masked faces, were encoded. When matching two simultaneously presented faces 5,6 , sensitivity (d') decreased when one or both faces were masked, while response bias varied across experiments.Pre-COVID-19 studies predicted more limited, or even an absence of, impairment to face identification, despite their focus on occluding single lower features (e.g. occluding the mouth alone).…”
mentioning
confidence: 99%
“…Marini et al 4 demonstrated that unoccluded faces were reidentified more accurately when unoccluded faces, rather than masked faces, were encoded. When matching two simultaneously presented faces 5,6 , sensitivity (d') decreased when one or both faces were masked, while response bias varied across experiments.…”
mentioning
confidence: 99%